2017
DOI: 10.18535/ijsrm/v5i6.29
|View full text |Cite
|
Sign up to set email alerts
|

Suppliers of Organic Food: Evidence From Sisli And Kartal Ecological Bazaars Of Istanbul

Abstract: The primary objective of this study was to determine the current state of affairs of organic product suppliers in two 100% ecological bazaars of Istanbul, Turkey. The data were collected by administering a questionnaire to 58 organic product suppliers in 100% ecological bazaars of Sissle and Karta. The results show that the organic farmers have a higher educational level and are younger as compared to the conventional farmers. The primary sources of information about organic farming are other farmers and fello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Earlier works of Ayan et al [1], Ayan et al [2], Boz and Rasulov [16], Boz and Kaynakçı [17] and Kilic and Eryilmaz [18], as well as official…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier works of Ayan et al [1], Ayan et al [2], Boz and Rasulov [16], Boz and Kaynakçı [17] and Kilic and Eryilmaz [18], as well as official…”
Section: Methodsmentioning
confidence: 99%
“…Although every human being deserve to eat healthy food, there is no justice and fair trade in organic food markets, particularly in developing countries. While high income consumers can afford to buy and consume organic products, other segments of the population have difficulties even to taste these products [1,2]. Developed countries particularly in Europe and North America consist of about 90 percent of the sales of organic and fairtrade products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is expected that consumers who have a higher tendency towards sustainable consumption tend to buy organic foods. Ayan et al (2017) also found that consumers think organic food is healthier than conventional alternatives. The study of Oraman & Unakıtan (2010) points out that concern for human health and safety are significant motivators of choosing organic food.…”
Section: Organic Food As Sustainable Choicementioning
confidence: 99%
“…Althoug the Takhar province has suitable climatic and soil condition for rice production and the agricultural environment hasn't contaminated with chemicals and pesticides, sustainable organic rice cultivation couldn't be developed. Since most of the developing countries have similar potential for cultivating organic crops [17], [18], and developing organic bazaars for local consumers [19], the Takhar province should be utilize this opportunity which will help to increase rice selling prices.…”
Section: Issues and Solution Recommendations For Rice Production And mentioning
confidence: 99%